Empresses, Queens, and Letters: Finding a 'Female Voice' in Late Antiquity? - Hillner, Julia (Gender & History, 2019)
This article discusses twenty-six Latin and Greek letters dating to the fifth and sixth centuries CE, written under the name of empresses and queens and originating from the later Roman Empire, Ostrogothic Italy and Merovingian Gaul. Where these letters have received attention, scholars have usually approached them with the intention of analysing a single letter’s content for evidence of a specific woman’s biography. This article studies them as a corpus instead. Comparing them with the male letters most of them travelled with and using insights from linguistic research on gender-specific language in antiquity, the article argues that probably none of the letters expressed an individual woman's ‘authentic voice’. Written by the equivalent of modern speech-writers trained in adopting a female register, they are testimony to political strategies common to the late Roman and post-Roman world that used the female voice to publicly perform sentiments that male rulership on its own could not. They are therefore evidence for wider late antique trends towards male and female co-regency visible also in art and ceremony of the period. These female letters are a specific late antique art form, which nonetheless holds truths for all scholars of female writing in antiquity and the early Middle Ages.